2019
DOI: 10.1016/j.psep.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and analytical prediction of pressure and impulse from vented gas explosion in large cylindrical tanks

Abstract: This paper presents an extension of previous study on estimating the internal and external pressure and impulse from vented gas explosion in large cylindrical tanks. Unlike the smallmedium scale explosion from cylindrical tanks in previous work, explosion pressure and impulse from large-scale explosions are numerically and analytical investigated in this study.CFD simulations are conducted and validated by using experimental data. Sensitivity study on grid selection for large-scale explosion simulations is per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…e fan is the heart of the mine, providing fresh air for the mine, excluding contaminated air, reducing the occurrence of gas explosions, coal dust explosions, and other disasters, and playing a pivotal role in the safe construction of the mine [18,19]. At present, many experts in related fields have conducted much research in the process of gas explosion shock wave propagation and already have a lot of theoretical knowledge; for example, Li et al studied the explosion pressure and impact generated by large explosions through numerical simulation [20]; Ye et al conducted theoretical and experimental research on the propagation law of flame and shock wave in the bend [21]; Song revealed the invented new dynamic response characteristics and laws of the explosion door of the vertical wind shaft during the explosion impact [22].…”
Section: Mine Fansmentioning
confidence: 99%
“…e fan is the heart of the mine, providing fresh air for the mine, excluding contaminated air, reducing the occurrence of gas explosions, coal dust explosions, and other disasters, and playing a pivotal role in the safe construction of the mine [18,19]. At present, many experts in related fields have conducted much research in the process of gas explosion shock wave propagation and already have a lot of theoretical knowledge; for example, Li et al studied the explosion pressure and impact generated by large explosions through numerical simulation [20]; Ye et al conducted theoretical and experimental research on the propagation law of flame and shock wave in the bend [21]; Song revealed the invented new dynamic response characteristics and laws of the explosion door of the vertical wind shaft during the explosion impact [22].…”
Section: Mine Fansmentioning
confidence: 99%
“…Dadashzadeh et al (2014) proposed a new method to quantify the risk of combustion products dispersion phenomenon in a confined or semi-confined facility. Li and Hao (2019) investigated the explosion pressure and impulse from large-scale explosions by using experiments and FLACS.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars studied the influences of pipe length, pipe diameter, and space distance on gas explosion overpressure [19][20][21]. Li and Hao simulated the ignition and propagation characteristics of gas explosions by introducing basic chemical reactions [22]. Some scholars studied the propagation law of gas explosion shock waves in roadways with different turning angles and on bifurcated roadways [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%